Neoadjuvant PD-1/PD-L1 inhibitors combined with chemotherapy in gastric cancer and gastroesophageal junction adenocarcinoma: a systematic review and meta-analysis of single-arm studies - Jun Leng; Jun Leng; Min Liu; Min Liu; Qianwen Wang; Qianwen Wang; Huaiwu Jiang; Jin Chen (Frontiers in Medicine)
BackgroundNeoadjuvant chemotherapy, particularly neoadjuvant immunotherapy, has achieved significant progress in treating gastric cancer (GC) and gastroesophageal junction (GEJ) adenocarcinoma. While PD-1/PD-L1 inhibitors have improved survival outcomes in some patients, the efficacy of combining neoadjuvant chemotherapy with PD-1/PD-L1 inhibitors remains insufficiently validated.ObjectiveThis study aims to evaluate the efficacy and safety of neoadjuvant chemotherapy combined with PD-1/PD-L1 inhibitors in GC/GEJ adenocarcinoma and enhance statistical power through meta-analysis.MethodsWe systematically searched PubMed, Embase, Web of Science, and the Cochrane Library up to October 5, 2024, for original clinical studies on neoadjuvant PD-1/PD-L1 inhibitors combined with chemotherapy for GC/GEJ adenocarcinoma. Eligible studies were evaluated using the Methodological Index for Non-Randomized Studies (MINORS) Criteria. Meta-analysis was performed using R 4.4.2 software.ResultsA total of 12 studies involving 428 patients were included. The primary efficacy outcomes were pathological complete response (pCR) and major pathological response (MPR), while secondary outcomes included disease control rate (DCR) and the rate of lymph node downstaging to ypN0. The effect size (ES) for pCR was 20.94% [95% CI: 0.1698; 0.2518], and for MPR, the ES was 55.86% [95% CI: 0.4891; 0.6271]. Safety was evaluated using the incidence of grade ≥3 treatment-related adverse events (trAEs), immune-related adverse events (irAEs), postoperative complications, and R0 resection rate. The meta-analysis revealed that 406 patients underwent surgical intervention, with 88 achieving pCR. The pooled effect size for R0 resection rate was 95.2% [95% CI: 0.896; 0.989]. The ES values for grade ≥3 adverse events, immune-related adverse events, and postoperative complications were 0.54 [95% CI: 0.30; 0.77], 0.17 [95% CI: 0.07; 0.31], and 0.28 [95% CI: 0.15; 0.44], respectively.ConclusionNeoadjuvant PD-1/PD-L1 inhibitor-based chemotherapy demonstrates promising therapeutic efficacy and safety in patients with gastric and gastroesophageal junction (GEJ) cancer. However, limitations such as small sample sizes and insufficient follow-up duration in current studies highlight the need for further randomized controlled trials and multicenter research to establish optimal treatment strategies.Systamatic review registrationIdentifier, CRD42024619916.